On the use of the term, "discriminative stimulus, " in behavior analytic practice. (5th March 2021) - Axe, Judah B.; McCarthy‐Pepin, Melanie
Abstract: We have seen behavior analysts use the term, "discriminative stimulus (S D )" incorrectly, often equating it with an instruction in discrete trial training (DTT). We posit this incorrect use is because (1) the definition of "S D " is complex and (2) because the term is defined and used incorrectly in DTT manuals. We provide correct definitions of "S D " from textbooks, incorrect definitions and uses in DTT manuals, and recommendations for use of the term and other antecedent variable terms in behavior analytic practice.